Interactions between testicular serotoninergic, catecholaminergic, and corticotropin-releasing hormone systems modulating cAMP and testosterone production in the golden hamster - Frungieri, Monica Beatriz (2002)
We previously reported the presence of serotonin (5-HT) in testes from golden hamster, a photoperiodic species which is a useful model for the study of states of male (in)fertility. The aims of this study were to investigate: (1) the presence of intrinsic sources of 5-HT in the testis; (2) the role of 5-HT in in vitro androgen production; (3) the serotoninergic receptor subtypes in the testis, and (4) the existence of interactions among the 5-HT receptors and the testicular catecholaminergic and corticotropin-releasing hormone (CRH) systems. Immunohistochemical studies revealed the presence of tryptophan hydroxylase, a 5-HT-biosynthetic enzyme, in interstitial cells which show the characteristic punctate chromatin pattern of Leydig cells. We describe an inhibitory action of 5-HT on testosterone, dihydrotestosterone, and androstane-3alpha,17beta-diol production from testes of peripubertal and adult hamsters maintained in a long photoperiod (14/10 h light/dark), and adult animals exposed to a short photoperiod (6/18 h light/dark). By using several agonists and antagonists of 5-HT receptors, we characterized 5-HT1A and 5-HT2A receptor subtypes involved in the inhibitory action of this neurotransmitter on human chorionic gonadotropin stimulated cyclic adenosine monophosphate and testosterone production. CRH also produced a negative modulation of both parameters, but epinephrine and norepinephrine, through alpha1/beta1-adrenergic receptors, exerted a stimulatory action. 5-HT1A, 5-HT2, and CRH antagonists showed that the testicular activity of the serotoninergic system, but also the alpha1/beta1-adrenergic receptor system, is mediated by CRH. Moreover, interactions between the 5-HT2A receptor system and alpha1/beta-adrenergic receptors have been established. Thus, these data suggest that alpha1/beta1-adrenergic receptors are involved in the local regulatory action exerted by 5-HT on steroidogenesis through a 5-HT2-receptor-mediated response and the CRH system.